Total Synthesis of Gobiusxanthin Stereoisomers and Their Application to Determination of Absolute Configurations of Natural Products: Revision of Reported Absolute Configuration of Epigobiusxanthin - Yumiko Yamano; Kotaro Ematsu; Hiromasa Kurimoto; Takashi Maoka; Akimori Wada (Marine Drugs, 2014)
(3R)-Gobiusxanthin stereoisomers (1a–d) were synthesized by stereoselective Wittig reaction of the (3R)-C15-acetylenic tri-n-butylphosphonium salt 7 with C25-apocarotenal stereoisomers 5a,b and 14a,b bearing four kinds of 3,6-dihydroxy-ε-end groups. The validity of the reported stereochemistry of gobiusxanthin was demonstrated by the fact that the reported spectral data of natural gobiusxanthin were in agreement with those of synthetic (3R,3'S,6'R)-gobiusxanthin (1a). On the other hand, the reported CD spectral data of natural epigobiusxanthin, which has been assigned as (3R,3'R,6'R)-isomer (3'-epigobiusxanthin), were identical with those of synthetic (3R,3'S,6'S)-isomer 1d (6'-epigobiusxanthin) rather than those of the corresponding synthetic 3'-epi-isomer 1b. It was found that the stereochemistry at C3-position has little effect on the shape of their CD spectra. Thus, in order to reinforce the validity of the absolute configurations at C3-position of natural specimens, (3S,3'S,6'R)- and (3S,3'S,6'S)-stereoisomers 1e and 1f were also synthesized and a HPLC analytical method for four stereoisomers was established by using a column carrying a chiral stationary phase. The HPLC analysis has proven that the stereochemistry of the natural epigobiusxanthin is 3R,3'S,6'S.